The causal relationship between autoimmune diseases and osteoporosis: a study based on Mendelian randomization - Wu, Shaofeng; Ye, Zhen; Yan, Yi; Zhan, Xinli; Ren, Liang; Zhou, Chenxing; Chen, Tianyou; Yao, Yuanlin; Zhu, Jichong; Wu, Siling; Ma, Fengzhi; Liu, Lu; et al. (Frontiers in Endocrinology, 2023)
The relationship between different autoimmune diseases and bone mineral density (BMD) and fractures has been reported in epidemiological studies. This study aimed to explore the causal relationship between autoimmune diseases and BMD, falls, and fractures using Mendelian randomization (MR).The instrumental variables were selected from the aggregated statistical data of these diseases from the largest genome-wide association study in Europe.Specifically, 12 common autoimmune diseases were selected as exposure. Outcome variables included BMD, falls, and fractures. Multiple analysis methods were utilized 2 to comprehensively evaluate the causal relationship between autoimmune diseases and BMD, falls, and fractures. Additionally, sensitivity analyses, including Cochran's Q test, MR-Egger intercept test, and one analysis, were conducted to verify the result's reliability.Strong evidence was provided in the results of the negatively association of ulcerative colitis (UC) with forearm BMD. UC also had a negatively association with the total body BMD, while inflammatory bowel disease (IBD) depicted a negatively association with the total body BMD at the age of 45-60 years. Horizontal pleiotropy or heterogeneity was not detected through sensitivity analysis, indicating that the causal estimation was reliable.This study shows a negative causal relationship between UC and forearm and total body BMD, and between IBD and total body BMD at the age of 45-60 years. These results should be considered in future research and when public health measures and osteoporosis prevention strategies are formulated.